Pengaruh Latihan Angeled Leg Pressed dan Lying Leg Curls Terhadap Explosive Power Otot Tungkai Atlet Futsal Putra Universitas PGRI Madiun - Budi Utomo, Ardyansyah Arief (UIR Press, 2019)
This research aimed to examine the effect of angled leg pressed and lying leg curls training toward explosive limb muscle power of futsal athletes of Universitas PGRI Madiun. This research was conducted as quantitative approach which experimental design. Sample of this study were Futsal athletes of Universitas PGRI Madiun which numbered 45 male students. The instrument used was Vertical Jump test. The results of this study showed that there was improvement amount 5.16% of explosive power in of limb muscles of athletes after applying angled leg pressed training. Besides, the improvement of using explosive power of athletes’ leg muscles after applying lying leg curls training was 4.51%. Meanwhile, the differences effect between angled leg pressed and lying leg curls on explosive limb muscle power of male Futsal athletes at UNIPMA were -2.26667. This research result is expected to be an evaluation of athletes and coaches, especially Futsal athletes of Universitas PGRI Madiun, in order to improve their passing skill by using angled leg pressed and lying leg curls.